EFL reading comprehension and reading strategies of different genders - Neneng Islamiah; Yudha Aprizani; Iwan Perdana (Studies in English Language and Education, 2017)
Two of the most examined dimension of reading strategies that have an affective influence on different genders are cognitive strategy and metacognitive strategy. This study was aimed to find out whether reading comprehension using different strategies would have different result or not for the two different genders. The researchers used a quantitative causal-comparative research approach, and data were collected from two instruments: reading comprehension test and questionnaires. A number of 50 students (25 females and 25 males) from one of the universities in Banjarmasin participated in this study. The results showed that between the two types of strategies, the cognitive strategy was mostly favoured by the male students, and metacognitive strategy was favoured by the female students. Nevertheless, their metacognitive or cognitive reading strategies preference does not significantly differ in their reading comprehension score. The interaction between two independent variables did not significantly happen in this research. The choice of using certain reading strategy was not determined by the category of gender. In other words, a certain type of gender using a certain type strategy did not give better results in reading comprehension.